PENGARUH MOTIVASI KERJA DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR JASA PENILAI PUBLIK RUKY, SAFRUDIN, DAN REKAN CABANG TEBET JAKARTA SELATAN - Urifah Dwi Wangi; Theobaldus Boro Tura (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the influence of work motivation and work facilities on employee performance at the Ruky, Safrudin and Rekan Public Appraisal Services Office, Tebet Branch, South Jakarta, both partially and simultaneously. The study used an associative quantitative method with a saturated sample of 50 respondents. Data analysis techniques include instrument testing, classical assumption testing, simple linear regression, multiple linear regression, correlation coefficients, and determination coefficients. Hypothesis testing was carried out through t-tests and F-tests. The results showed that work motivation had a positive and significant effect on employee performance. This was evidenced by the regression equation Y = 18.047 + 0.370X1 + e and the tvalue of 7.916 > ttable 2.011. These findings indicate that increasing work motivation can significantly boost employee performance. Work facilities were also proven to have a positive and significant effect on employee performance, based on the regression equation Y = 18.047 + 0.215X2 + e and the t-value of 5.083 > t-table 2.011. Simultaneously, work motivation and work facilities have a significant influence on employee performance, which is shown through the regression equation Y = 18.047 + 0.370X1 + 0.215X2 + e. The correlation coefficient (R) of 0.894 indicates a very strong relationship, while the determination coefficient (R²) of 0.791 indicates that both variables contribute 79.1% to employee performance, and the remaining 20.9% is influenced by other factors. The F test obtained a calculated F value of 93.492 > Ftable 3.20, so overall it can be concluded that work motivation and work facilities have a positive and significant influence on employee performance.